Xanthophylls from the sea: Algae as source of bioactive carotenoids - González Pereira, Antía (2018)
Algae are considered pigment-producing organisms. The function of these compounds in algae is to carry out photosynthesis. They have a great variety of pigments, which can be classified into three large groups: chlorophylls, carotenoids, and phycobilins. Within the carotenoids are xanthophylls. Xanthophylls (fucoxanthin, astaxanthin, lutein, zeaxanthin, and β-cryptoxanthin) are a type of carotenoids with anti-tumor and anti-inflammatory activities, due to their chemical structure rich in double bonds that provides them with antioxidant properties. In this context, xanthophylls can protect other molecules from oxidative stress by turning off singlet oxygen damage through various mechanisms. Based on clinical studies, this review shows the available information concerning the bioactivity and biological effects of the main xanthophylls present in algae. In addition, the algae with the highest production rate of the different compounds of interest were studied. It was observed that fucoxanthin is obtained mainly from the brown seaweeds Laminaria japonica, Undaria pinnatifida, Hizikia fusiformis, Sargassum spp., and Fucus spp. The main sources of astaxanthin are the microalgae Haematococcus pluvialis, Chlorella zofingiensis, and Chlorococcum sp. Lutein and zeaxanthin are mainly found in algal species such as Scenedesmus spp., Chlorella spp., Rhodophyta spp., or Spirulina spp. However, the extraction and purification processes of xanthophylls from algae need to be standardized to facilitate their commercialization. Finally, we assessed factors that determine the bioavailability and bioaccesibility of these molecules. We also suggested techniques that increase xanthophyll's bioavailability.